ANALYSIS OF DETERMINING CRITICAL COMPONENTS USING FMECA METHOD IN SEAWATER PUMP OF DIESEL GENERATOR CATERPILLAR 3412 - Saiful Hasan; Erpan Sahiri; Suprayitno Suprayitno; Endin Tri Hartanto (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
The seawater pump on the Caterpillar 3412 Diesel Generator is one of the important component to make the Diesel generator can work well. This section serves to circulate seawater for the heat transfer process. The seawater pump is part of a cooling system of the engine which keeps the engine temperature from being too overheat. Seawater pumps with continuous operational conditions, resulting in reduced component reliability. This study applies the FMECA method to identify opportunities for failure at the seawater pump. From the calculation of FMECA, it is obtained an assessment of the level of risk from a failure model that can give priority scale to preventive maintenance that can be done in the future. FMECA analysis of 27 components in seawater pump on the Diesel Generator, found 7 components that had RPN values above the average. The following are the 4 components with the highest RPN value, namely Shaft (7C-3493) RPN value 420,44; Key (175-6716) RPN value 300,31; Bearing Inner (4M-6107) RPN value 285 and Bearing Roller (3N-8463) RPN value 253,13. Components that have high RPN values require more attention, such as routine checks and periodic maintenance.Keyword: Seawater pump, Caterpillar 3412 Diesel Generator, FMECA, RPN.